Response Surface Methodology (RSM) for analysing culture conditions of Acidocella facilis strain USBA-GBX-505 and Partial Purification and Biochemical Characterization of Lipase 505 LIP - Luisa Fernanda Bernal; Gina Lopez, Monica Ruiz; Ricardo Vera-Bravo; Alejandro Reyes; Sandra Baena; Monica Ruiz (Universitas Scientiarum)
Using Response Surface Methodology (RSM) we evaluated the culture conditions (nitrogen source, carbon source, pH and agitation rate) that increase the biomass of Acidocella facilis strain USBA-GBX-505 and therefore enhance the production of its lipolytic enzyme, 505 LIP. RSM results revealed that yeast extract and agitation were key culture factors that increased the growth-associated lipolytic activity by 4.5-fold (from 0.13 U.mg-1 to 0.6 U.mg-1). The 505 LIP lipase was partially purified using size-exclusion chromatography and ion-exchange chromatography. Its molecular weight was >77 kDa. The enzyme shows its optimum catalytic activity at 55 °C and pH 7.5. EDTA, PMSF, 1-butanol and DMSO inhibited enzymatic activity, whereas Tween 20, acetone, glycerol and methanol increased it. Metallic ions are not required for the activity of 505 LIP, and even have an inhibitory effect on the enzyme. This study shows the potential use of A. facilis strain USBA-GBX-505 for the production of a newly identified lipolytic enzyme, 505 LIP, which is stable at moderate temperatures and in the presence of organic solvents. These are important characteristics for the synthesis of many useful products.